Conflictualité autour des marqueurs temporels : sociohistoire de 25 ans du mouvement Notav - Anahita Grisoni (VertigO, 2015)
The Italian Notav movementis self-defined as a « popularmovement ». Since 25 years, it’s opposed to the construction of a High Speed railway in the Susa Valle (Piedmont). This article follows closely the discourses and practices of the ecologists stakeholders of the movement. Itunderlines how their representations challenge time markers of modernity : presentism (Hartog, 2003, 2012) and acceleration (Rosa, 2012) and how they are structural to the conflict. This world view is opposed to an other Weltanschauung, present in public claims as in individual lifestyles, that carries the idea of a « voluntarydeceleration » renewing the meanings of the concept of "multiple modernities" (Eisenstadt, 2000). Beyond this critical dimension, the article focuses on the different stages of Notav movement space-time evolution, which allows to highlight the sense of struggle within the frame of the European crisis.